Effect of Planting Dates on Growth and Yield of True Potato Seed (TPS) in Nursery Raising Approach - M.M. Rahman Jamro; S.D. Tunio; U.A. Buriro; Q.D. Chachar (Journal of Basic & Applied Sciences, 2015)
To determine the proper planting dates for true potato seed (TPS) nursery, the present study was conducted at Agriculture Research Institute, Tandojam, Pakistan located at 25.24, 46.00,’N and 68.32, 12.00’E during 2009 and 2010. Comparison of three planting dates i.e. October 15, October 30 and November 15, were made. The results obtained from m-2 area showed maximum germination (84.95%), plant height (46.94 cm) average number of micro (1-9 mm) tubers (196.1), small(10-19 mm) tubers (42.15), medium(20-39 mm) tubers (26.56), large(>40 mm) tubers (7.57), weight of micro tubers (1302 g), small tubers (480.3 g), medium tubers (340 g) and large tubers (468.5 g) were observed when TPS-9804 was planted on 30th October. The overall results for tuber yield showed that TPS-9804 genotype planted on 30thOctober produced maximum tuber yield (29.46 t ha1) as compared to rest of genotypes; hence, TPS-9804 genotype is recommended for raising of TPS nursery with 30th October of planting date.